The genus Entomophthora: bringing the insect destroyers into the twenty-first century - Carolyn Elya (BMC, 2021)
Abstract The fungal genus Entomophthora consists of highly host-specific pathogens that cause deadly epizootics in their various insect hosts. The most well-known among these is the “zombie fly” fungus E. muscae, which, like other Entomophthora species, elicits a series of dramatic behaviors in infected hosts to promote optimal spore dispersal. Despite having been first described more than 160 years ago, there are still many open questions about Entomophthora biology, including the molecular underpinnings of host behavior manipulation and host specificity. This review provides a comprehensive overview of our current understanding of the biology of Entomophthora fungi and enumerates the most pressing outstanding questions that should be addressed in the field. We briefly review the discovery of Entomophthora and provide a summary of the 21 recognized Entomophthora species, including their type hosts, methods of transmission (ejection of spores after or before host death), and for which molecular data are available. Further, we argue that this genus is globally distributed, based on a compilation of Entomophthora records in the literature and in online naturalist databases, and likely to contain additional species. Evidence for strain-level specificity of hosts is summarized and directly compared to phylogenies of Entomophthora and the class Insecta. A detailed description of Entomophthora’s life-cycle and observed manipulated behaviors is provided and used to summarize a consensus for ideal growth conditions. We discuss evidence for Entomophthora’s adaptation to growth exclusively inside insects, such as producing wall-less hyphal bodies and a unique set of subtilisin-like proteases to penetrate the insect cuticle. However, we are only starting to understand the functions of unusual molecular and genomic characteristics, such as having large > 1 Gb genomes full of repetitive elements and potential functional diploidy. We argue that the high host-specificity and obligate life-style of most Entomophthora species provides ample scope for having been shaped by close coevolution with insects despite the current general lack of such evidence. Finally, we propose six major directions for future Entomophthora research and in doing so hope to provide a foundation for future studies of these fungi and their interaction with insects.